Wastewater Treatment Case Study - SEAU Braila - Lucica BALINT (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2018)
The paper analyses the influent and effluent parameters, as well as the efficiency of the purification process. CBO5 is found to be within the legal limits in terms of the amount of effluent suspensions of max 6.0 mg/L O2. The efficiency of their removal from the influent was at least 94.8%. CCO is observed within the legal limits of the amount of effluent suspensions of max 20.2 mg/L O2. The efficiency of their removal from the influent was at least 93.0%. Suspended matter shows that the effluent sludge was within the legal limits of max 10.9 mg/L, and the efficiency of their removal from the influent was at least 91.6%. Total nitrogen (Ntotal) and total phosphorus (Ptotal) are exceedances of the limits for sensitive areas subject to eutrophication. A downstream denitrification step is proposed downstream of the aerobic stage to eliminate total nitrogen, and a phase of chemical treatment or alternation of aerobic and anoxic steps is proposed for the removal of total phosphorus.